China's economic development: Growth and structural change - "Cheng , Chu - Yuan" (Colorado;Westview Press, 1984)
How has the government of the PRC transformed traditional economic institutions into a socialist, central-planning system? What has been the impact of this transformation on China$1 (Bs economic growth? What is the essence of the Chinese development model and how successfully has it functioned during the past three decades? etc. have been explained in the books
Keywords: Economic development-China